A cross sectional study on depression among paramedical students in MES Institute of Paramedical Sciences - Suresh, Atul; G., Nandini; Rajeev, Krishnaraj; Salim, Ashid; P. T., Mohamed Jawad (International Journal of Research in Medical Sciences, 2023)
Background: Depression is characterized by persistent sadness and a lack of interest or pleasure in previously rewarding or enjoyable activities. It is very important to identify the factors predisposing to depression among paramedical students. The main objective of this study was to assess the prevalence of depression and the factors associated with depression among the paramedical students. Methods: A cross-sectional study was done among all the 208 paramedical students studying in MES using a predesigned questionnaire along with Beck’s depression inventory tool to identify depression. Chi-square test and multivariate regression analysis were used to find the association between variables. Results: The prevalence of depression was found to be 24.5%. 11.54 % of the total study participants have borderline depression, while 10.58%, 1.92% and 0.48 % had moderate, severe and extreme form of depression respectively. Chi square test showed type of family, course of study, smoking habits, traumatic events in the past, bad interpersonal relationship, concern regarding the future were found to be statistically associated with depression. In multivariate analysis, bad interpersonal relationship between friends and family members (OR= 3.13), worrying about the future (OR=6.03) and those who never sought any form of help for mental stress (OR=1.5) were the risk factors identified. Conclusions: Course selection, type of family they came from, any traumatic events in the past, lack of interpersonal relationship between friends, worrying about the job opportunities after completing the course, not seeking help for mental stress were the factors contributing towards depression.